Peningkatan Kepedulian Lingkungan melalui Pemasangan Poster Edukasi di Desa Lam Keumok - Vivi Silvia; Teuku Muhammad Taufiqurrahman; Sofiaturrahmi Sofiaturrahmi; Fadhilal Ahmad (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service initiative aimed to enhance public awareness in Lam Keumok Village regarding environmental cleanliness and health through the installation of educational posters. The project was motivated by the prevalence of environment-related diseases and limited public access to effective visual information. The method used was educational and observational with limited participatory engagement. Poster were designed to be visually appealing and easily understood, then placed in strategic public locations such as village halls and places of worship. Observations revealed increased public engagement, marked by spontaneous interactions like reading and discussing the posters. The media proved effective in directly conveying messages, strengthening collective awarenes, and fostering civic involvement. Use of local language and contextual visuals ensured message clarity. Despite the short implementation period, the long-term potential impact is promising as repeated visual exposure can influence behavioral change. The findings conclude that educational posters are a powerful communication tool in rural areas and suggest the strategi can be replicated in similar settings. Community participation in content planning was a key factor in enhancing ownership and ensuring program sustainability.